2023
DOI: 10.3390/ijms242015124
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of Myostatin in a Mouse Model of Typical Nemaline Myopathy Increases Muscle Size and Force

Johan Lindqvist,
Henk Granzier

Abstract: Nemaline myopathy is one of the most common non-dystrophic congenital myopathies. Individuals affected by this condition experience muscle weakness and muscle smallness, often requiring supportive measures like wheelchairs or respiratory support. A significant proportion of patients, approximately one-third, exhibit compound heterozygous nebulin mutations, which usually give rise to the typical form of the disease. Currently, there are no approved treatments available for nemaline myopathy. Our research explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…[26][27][28][29][30][31] It has also been implicated in the regulation of thin filament length (TFL), as reduced levels of nebulin protein have been associated with shortened TFL in patients with NEB-related nemaline myopathy, as well as in nebulin-deficient mouse models, zebrafish, and chick skeletal myocytes. 30,[32][33][34][35][36][37][38][39] Despite investigating a number of therapeutic interventions including troponin activators such as Levosimendan, 40 CK-20066260, 30 dietary supplements 41 and myostatin inhibitors, 42,43 there are currently no effective therapies targeting the underlying pathological mechanisms for nebulinbased NEM (NEM2). It has been shown that Omecamtiv mecarbil (OM), a selective smallmolecule activator of cardiac myosin (MYH7) that was initially developed as a treatment for heart failure, 44,45 , increases submaximal force production in type I skeletal muscles of Neb cKO mouse model 46 and rat diaphragm.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31] It has also been implicated in the regulation of thin filament length (TFL), as reduced levels of nebulin protein have been associated with shortened TFL in patients with NEB-related nemaline myopathy, as well as in nebulin-deficient mouse models, zebrafish, and chick skeletal myocytes. 30,[32][33][34][35][36][37][38][39] Despite investigating a number of therapeutic interventions including troponin activators such as Levosimendan, 40 CK-20066260, 30 dietary supplements 41 and myostatin inhibitors, 42,43 there are currently no effective therapies targeting the underlying pathological mechanisms for nebulinbased NEM (NEM2). It has been shown that Omecamtiv mecarbil (OM), a selective smallmolecule activator of cardiac myosin (MYH7) that was initially developed as a treatment for heart failure, 44,45 , increases submaximal force production in type I skeletal muscles of Neb cKO mouse model 46 and rat diaphragm.…”
Section: Introductionmentioning
confidence: 99%